Treatment of lamivudine-resistant hepatitis B infection in post-renal transplant patients with Adefovir dipivoxil: preliminary results - de Silva, H.J.; Dassanayake, A.S.; Manamperi, A.; de Silva, A.P. (Elsevier, 2006)
We report the treatment outcome in six post-renal transplant patients with lamivudine-resistant hepatitis B virus (LR-HBV) infection using adefovir dipivoxil and followed for 6 to 18 months. Posttransplant immunosuppressive therapy was not altered. Adefovir dipivoxil effectively suppressed hepatitis B virus DNA and improved alanine transferase, although DNA suppression seemed dependent on continued therapy. Nephrotoxicity led to withdrawal of the drug in three patients. This may limit therapeutic usefulness in a significant proportion of post-renal transplant patients with LR-HBV infection.
Indexed in MEDLINE